Skammen og dens brødre: Arbejdsløshed, maskulinitet og klasseskam - Aarhus, Mathies Græsborg (K&K - Kultur og Klasse, 2018)
This article is about how it feels to be an unemployed man today. After briefly accounting for certain historical developments that have shaped the contemporary unemployed male experience, the article focuses on one feeling central to this experience: shame. The article argues that unemployment is increasingly attached to shame, rather than guilt, as the unemployed self perceives itself as inadequate in relation to a neoliberal ideal of entrepreneurship. Using sociological theories about class shame, the article proceeds to analyze two literary representations of unemployed men in a contemporary Danish context: Lau Aaen’s Dagpengeland and Jens Blendstrup’s Slagterkoner og Bagerenker. The shame in Dagpengeland breeds a critical attitude towards the shaming unemployment institutions of the welfare state, while Slagterkoner og Bagerenker explores the psychological processes of a form of shame turned into xenophobic resentment. Unemployed male shame is thus described as a multifaceted feeling; destructive in the sense that it tears down men’s ingrained identities and solidarities but productive in the sense that it affectively confronts the ashamed subject with certain social inequalities and injustices.